PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PEMETAAN ANCAMAN BANJIR DI KOTA DENPASAR - Made Pasek Oka Adnyana; Atmaja, Dewa Made; Budiarta, I Gede; Kurniawan, Wayan Damar Windu; Jayantara, I Gst Ngr Yoga (Jurnal ENMAP (Environment and Mapping), 2024)
Denpasar City is the capital of Bali Province, located in the southern part of Bali Island. The population growth rate in Denpasar City from 2021 to 2022 reached 0.12%, with a population density of 5,727 people per square meter in 2022. This high population growth rate naturally impacts the demand for land for both residential and activity purposes, indirectly posing a potential risk for flooding problems. According to BPBD Denpasar City, there were 37 flood incidents in 2018 and 5 flood incidents in 2020. This study aims to map flood threats in Denpasar City, Bali Province. The method used is the Analytical Hierarchy Process (AHP), which assigns weights and scores to each flood parameter and then overlays them. The weighting and scoring of each flood parameter are based on related research. The flood parameters used include slope gradient, land cover, rainfall, drainage density, and soil type. The overlay results produce a flood threat map with five classifications: very low with an area of 1.17 ha, low with an area of 121.35 ha, medium with an area of 2210.41 ha, high with an area of 6970.29 ha, and very high with an area of 3178.92 ha.